NOTE ON SCALING OF PEAK GROUND ACCELERATION AND PEAK GROUND VELOCITY WITH MAGNITUDE - Douglas J. (My University, 2002)
The theoretical scaling of near-field peak ground acceleration and peak ground velocity with moment magnitude, Mw , is found using an L model of rupture. This scaling matches well with the magnitude scaling of recent attenuation relations.
Keywords: EARTHQUAKES; FAULT MODELS; STRONG GROUND MOTION